God and the Oval Office : the religious faith of our 43 presidents - McCollister, John, 1935- (Nashville, Tenn. : W Pub. Group, 2005)
"Presents information regarding each United States president and how their faith influenced them"--Provided by publisher.
Keywords: Presidents -- United States -- Religion